SHALAHUDDIN AL-'Aá¸ŒLABI Analisis Metodologi Kritik Matan HadÄ«á¹¡ Terhadap Riwayat Yang Bertentangan Dengan Akal, Indra dan Sejarah - Muhammad Nabat Ardli; Reza Hilmy Luayyin (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2024)
Research on HadÄ«á¹¡ cannot be separated from two main elements, called sanad and matan. Among HadÄ«á¹¡ scholars, research on sanad receives more attention than matan, which prompted Salahuddin al-'Aá¸labi to write the book